Age and Depression in a Nationally Representative Sample of Canadians: A Preliminary Look at the National Population Health Survey - Wade, Terrance J. (Can J Public Health, 1997)
There are considerable inconsistencies in the literature concerning the relationship between age and depression. Recently, however, two independent studies in the, U.S. have shown that the distribution is U-shaped with the lowest reported levels of depression at ages 45–49. Three reasons for past inconsistencies are identified and addressed using the 1994 National Population Health Survey by Statistics Canada. Using both a distress scale and a diagnostic measure, a substantially different relationship was found. The prevalence of distress decreased steadily with age until about 65, with only a slight increase afterwards for both males and females. After the introduction of several sociodemographic covariates, however, this relationship was clearly negative. These findings are discussed in terms of future research questions.